Evaluate the environmental footprint of treated municipal sludge - Goh, Siew Yinn (2024)

(untitled)
Sludge management presents a significant challenge in the wastewater sector, particularly with the escalating human population leading to increased sludge generation, resulting in waste management issues. In response, many developed countries are shifting towards sustainable practices, utilising technology and exploring alternative methods for treating and disposing of municipal sludge, aiming to phase out landfilling and embrace resource recovery. Life Cycle Assessment (LCA) emerges as a crucial tool in enabling a comprehensive analysis of each process stage to identify the environmental hotspots and drive sustainable development. However, Malaysia lacking comprehensive policies and regulations for resource recovery in the water sector, with limited comparative LCA studies assessing the environmental impacts of various sludge management practices in wastewater treatment plants. This study provides an overview of sludge management in Malaysian wastewater treatment plants and applied LCA to assess its environmental performance. The objectives of the study are to identify the life cycle inventory of sludge management using GaBi software and evaluate the environmental impact indicators of different sludge management using the CML2001 method. LCA of the study was conducted in a gateto-grave manner, which focused on sludge management from sludge dewatering to its end life. The input and output data for the sludge management process were sourced from a site study conducted at a wastewater treatment plant in Kuala Lumpur, supplemented by the GaBi database and literature sources. Global Warming Potential, Abiotic Depletion (fossil), Acidification Potential, Human Toxicity and Marine Aquatic Ecotoxicity Potential were the five environmental impact indicators analysed in this study. The life cycle inventory analysis (LCIA) revealed that landfilling presented the highest environmental impacts due to methane emissions from landfill degradation and leachate contamination, while incineration offered waste volume reduction and was sustainable for energy recovery but posed air pollution risks. Land application of sewage sludge demonstrated the lowest environmental impacts by substituting fertiliser. However, there was a risk of human toxicity due to the presence of heavy metals. For Global warming potential indicator, landfilling yielded the highest (1084.56 kg CO2, eq), followed by incineration (220.09 kg CO2, eq) and land application (182.06 kg CO2, eq). Acidification potential indicator showed that landfilling exhibiting higher value than land application (0.221 kg SO2 eq and 0.916 kg SO2 eq respectively). Overall, land application emerged as the most sustainable alternative for sludge management for the wastewater sector, offering the potential for adoption to promote environmental sustainability